2016
DOI: 10.1016/j.otsr.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic TKA using navigation: Surgical technique and initial results

Abstract: IV (retrospective case series review).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 27 publications
2
107
0
3
Order By: Relevance
“…Early studies comparing MA and KA TKA have demonstrated either equivalent or better clinical outcomes for KA TKA [7][8][9][10][11][12]. This may be because KA TKA produces more neutral weight bearing positions and decreased knee adduction moment, a surrogate for medial tibiofemoral joint loading and thus implant durability when compared to MA TKA [13,14], or it may result from less disruption of the native soft tissue envelope [15][16][17]. The KA technique attempts to modify implant position in order to recreate the anatomy of the prearthritic articular surface for the individual patient.…”
Section: Introduction/purposementioning
confidence: 99%
“…Early studies comparing MA and KA TKA have demonstrated either equivalent or better clinical outcomes for KA TKA [7][8][9][10][11][12]. This may be because KA TKA produces more neutral weight bearing positions and decreased knee adduction moment, a surrogate for medial tibiofemoral joint loading and thus implant durability when compared to MA TKA [13,14], or it may result from less disruption of the native soft tissue envelope [15][16][17]. The KA technique attempts to modify implant position in order to recreate the anatomy of the prearthritic articular surface for the individual patient.…”
Section: Introduction/purposementioning
confidence: 99%
“…Femoral external rotation was set at 3° to the femoral posterior condyles. With regarding to the KA-TKA, a restricted KA protocol described by Hutt et al [9] was conducted in our institution. The HKA angles were limited for the KA-TKA from 6° varus to 3° valgus.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…The main outcome was Knee Society Score (KSS) 2011 [10], including symptom (0-25), satisfaction (0-40), expectation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and functional activities (0-100) at the 1-year followup. Secondary outcomes included the range of motion (ROM) and HKA angle.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Femoral external rotation was set at 3° to the femoral posterior condyles. With regard to the KA-TKA, a modi ed KA protocol described by Hutt et al [9] was conducted in our institution. The bone cut was modi ed from patient anatomy, which was conducted as planned using the portable navigation system.…”
Section: Surgical Techniquesmentioning
confidence: 99%